Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How to show that $\phi_a(z)=\frac{z-a}{1-\bar{a}z}$ is mapping $\phi_a(z):\mathbb{D} \rightarrow \mathbb{D}$? So how to show that if $|z| \leq 1,\forall z\in \mathbb{C}$, then $|\phi_a(z)| \leq 1$?

I tried to make standard stuff, but got stuck. $|\frac{z-a}{1-\bar{a}z}| =\frac{|z-a|}{|1-\bar{a}z|}... $

Just some hint please, whether it is able to solve the way I showed or not.

share|cite|improve this question
up vote 3 down vote accepted
  1. It is only possible if $|a|<1$ otherwise $|\phi_a(0)|\geq 1$.

You can also use properties of the Möbius transformation. Not it suffices to show that three points out of $\mathbb{S}_1(0):=\{z ||z|=1\}$ are mapped onto itself. Choose for example$z=1,i,-1$. Then you know that the whole sphere is mapped onto itself. Explotiong that and $\phi_a(0)\subset \mathbb{D}$ you obtain by a property of Möbius transformations that $\mathbb{D}$ is mapped onto itself

However it is quiet similar to the solution of K.Stm. but with a slightly different argumentation

share|cite|improve this answer

If $|\tfrac{0-a}{1-\overline{a}·0}| < 1$, then $ϕ_a(0) ∈ \mathbb{D}$. For $|z| = 1$, you have: $$|z-a|^2 = (z-a)\overline{(z-a)} = 1 - a\overline{z} - z\overline{a} + a\overline{a} = (1 - \overline{a}z)\overline{(1-\overline{a}z)} = |1-\overline{a}z|^2$$

The inverse of $ϕ_a$ is given by $ϕ_{-a}$, so $|z| = 1 ⇔ |ϕ_a(z)| = 1$ or $ϕ_a(S_1) = S_1$, this already somehow shows the assertion, just make it precise:

Since $ϕ_a$ is continuous, the connected component of $0$ in $ℂ \setminus S_1$, viz $\mathbb{D}$, must lie in the connected component of $ϕ_a(0)$ in $ϕ_a (ℂ \setminus S_1) = ℂ \setminus S_1$. But if $ϕ_a(0) ∈ \mathbb{D}$, then $ϕ_a(\mathbb{D}) ⊂ \mathbb{D}$.

share|cite|improve this answer
$(1-\bar{a}z)\bar{(1-\bar{a}z)}=(1-\bar{a}z)(1-\bar{z}a) =1(1-\bar{z}a)-\bar{a}z(1-\bar{z}a)=1-\bar{z}a-\bar{a}z+\bar{a}az\bar{z}=...$ok. – alvoutila Mar 9 '13 at 12:57

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.